Cardiovascular risk of sitagliptin in ischemic stroke patients with type 2 diabetes and chronic kidney disease: A nationwide cohort study - Liang, Chung-Yu (Medicine (Baltimore), 2018)
Limited data are available about the cardiovascular (CV) safety and efficacy of sitagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor, in ischemic stroke patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD). Ischemic stroke patients with T2DM and CKD were selected from the Taiwan National Health Insurance Research Database (NHIRD) from March 1, 2009 to December 31, 2011. A total of 1375 patients were divided into 2 age- and gender-matched groups: patients who received sitagliptin (n = 275; 20%) and those who did not (n = 1,100). Primary major adverse cardiac and cerebrovascular events (MACCE), including ischemic stroke, hemorrhagic stroke, myocardial infarction (MI), or CV death, were evaluated. During a mean 1.07-year follow-up period, 45 patients (16.4%) in the sitagliptin group and 165 patients (15.0%) in the comparison group developed MACCEs (Hazard ratio [HR] 1.05; 95% confidence interval [CI], 0.75–1.45). Compared to the non-sitagliptin group, the sitagliptin group had a similar risk of ischemic stroke (HR 0.82; 95% CI, 0.51–1.32.), hemorrhagic stroke (HR 1.50; 95% CI, 0.58–3.82), MI (HR 1.14; 95% CI, 0.49–2.65), and CV mortality (HR 1.06; 95% CI, 0.61–1.85). The use of sitagliptin in recent ischemic stroke patients with T2DM and CKD was not associated with increased or decreased risk of adverse CV events.